Difference between revisions of "009B Sample Midterm 3, Problem 2"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam">State the fundamental theorem of calculus, and use this theorem to find the derivative of ::<math>F(x)=\int_{\cos (x)}^5 \frac{1}{1+u^{10}}~du.</math> {...")
 
Line 7: Line 7:
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|What does Part 1 of the Fundamental Theorem of Calculus say is the derivative of <math style="vertical-align: -16px">G(x)=\int_x^5 \frac{1}{1+u^{10}}~du?</math>
+
|What does Part 1 of the Fundamental Theorem of Calculus  
 +
|-
 +
|say is the derivative of &nbsp;<math style="vertical-align: -16px">G(x)=\int_x^5 \frac{1}{1+u^{10}}~du?</math>
 
|-
 
|-
 
|
 
|
::First, we need to switch the bounds of integration.  
+
&nbsp;&nbsp;&nbsp;&nbsp; First, we need to switch the bounds of integration.  
 
|-
 
|-
 
|
 
|
::So, we have <math style="vertical-align: -16px">G(x)=-\int_5^x \frac{1}{1+u^{10}}~du.</math>
+
&nbsp;&nbsp;&nbsp;&nbsp; So, we have &nbsp;<math style="vertical-align: -16px">G(x)=-\int_5^x \frac{1}{1+u^{10}}~du.</math>
 
|-
 
|-
 
|
 
|
::By Part 1 of the Fundamental Theorem of Calculus, <math style="vertical-align: -16px">G'(x)=-\frac{1}{1+x^{10}}.</math>  
+
&nbsp;&nbsp;&nbsp;&nbsp; By Part 1 of the Fundamental Theorem of Calculus, &nbsp;<math style="vertical-align: -16px">G'(x)=-\frac{1}{1+x^{10}}.</math>  
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 26: Line 29:
 
|-
 
|-
 
|
 
|
:Let <math style="vertical-align: -5px">f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt.</math>
+
Let &nbsp;<math style="vertical-align: -5px">f</math>&nbsp; be continuous on &nbsp;<math style="vertical-align: -5px">[a,b]</math>&nbsp; and let &nbsp;<math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt.</math>
 
|-
 
|-
 
|
 
|
:Then, <math style="vertical-align: -1px">F</math> is a differentiable function on <math style="vertical-align: -5px">(a,b)</math> and <math style="vertical-align: -5px">F'(x)=f(x).</math>
+
Then, &nbsp;<math style="vertical-align: -1px">F</math>&nbsp; is a differentiable function on &nbsp;<math style="vertical-align: -5px">(a,b)</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">F'(x)=f(x).</math>
 
|-
 
|-
 
|'''The Fundamental Theorem of Calculus, Part 2'''
 
|'''The Fundamental Theorem of Calculus, Part 2'''
 
|-
 
|-
 
|
 
|
:Let <math style="vertical-align: -5px">f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -1px">F</math> be any antiderivative of <math style="vertical-align: -5px">f.</math>
+
Let &nbsp;<math style="vertical-align: -5px">f</math>&nbsp; be continuous on &nbsp;<math style="vertical-align: -5px">[a,b]</math>&nbsp; and let &nbsp;<math style="vertical-align: -1px">F</math>&nbsp; be any antiderivative of &nbsp;<math style="vertical-align: -5px">f.</math> Then,
 
|-
 
|-
 
|
 
|
:Then, <math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a).</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a).</math>
 
|}
 
|}
  
Line 43: Line 46:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|First, we have
+
|First,
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -15px">F(x)=-\int_5^{\cos (x)} \frac{1}{1+u^{10}}~du.</math>
::<math style="vertical-align: -15px">F(x)=-\int_5^{\cos (x)} \frac{1}{1+u^{10}}~du.</math>
 
 
|-
 
|-
|Now, let <math style="vertical-align: -5px">g(x)=\cos(x)</math> and <math style="vertical-align: -15px">G(x)=\int_5^x \frac{1}{1+u^{10}}~du.</math>  
+
|Now, let &nbsp;<math style="vertical-align: -5px">g(x)=\cos(x)</math>&nbsp; and &nbsp;<math style="vertical-align: -15px">G(x)=\int_5^x \frac{1}{1+u^{10}}~du.</math>  
 
|-
 
|-
|So,  
+
|Therefore,  
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -5px">F(x)=-G(g(x)).</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -5px">F(x)=-G(g(x)).</math>
 +
|-
 +
|Hence,
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -5px">F'(x)=-G'(g(x))g'(x)</math>  
 
|-
 
|-
|Hence, <math style="vertical-align: -5px">F'(x)=-G'(g(x))g'(x)</math> by the Chain Rule.
+
|by the Chain Rule.
 
|}
 
|}
  
Line 61: Line 67:
 
!Step 3: &nbsp;
 
!Step 3: &nbsp;
 
|-
 
|-
|Now, <math style="vertical-align: -5px">g'(x)=-\sin(x).</math>
+
|Now,  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -5px">g'(x)=-\sin(x).</math>
 
|-
 
|-
 
|By the Fundamental Theorem of Calculus,  
 
|By the Fundamental Theorem of Calculus,  
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -15px">G'(x)=\frac{1}{1+x^{10}}.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -15px">G'(x)=\frac{1}{1+x^{10}}.</math>
 
|-
 
|-
 
|Hence,
 
|Hence,
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{F'(x)} & = & \displaystyle{-\frac{1}{1+\cos^{10}x}(-\sin(x))}\\
 
\displaystyle{F'(x)} & = & \displaystyle{-\frac{1}{1+\cos^{10}x}(-\sin(x))}\\
 
&&\\
 
&&\\
Line 77: Line 85:
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|&nbsp;&nbsp; '''The Fundamental Theorem of Calculus, Part 1'''
+
|&nbsp; &nbsp; &nbsp; &nbsp; See Step 1 above
|-
 
|
 
:&nbsp;&nbsp; Let <math style="vertical-align: -5px">f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt.</math>
 
|-
 
|
 
:&nbsp;&nbsp; Then, <math style="vertical-align: -1px">F</math> is a differentiable function on <math style="vertical-align: -5px">(a,b)</math> and <math style="vertical-align: -5px">F'(x)=f(x).</math>
 
|-
 
|&nbsp;&nbsp; '''The Fundamental Theorem of Calculus, Part 2'''
 
|-
 
|
 
:&nbsp;&nbsp; Let <math style="vertical-align: -5px">f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -1px">F</math> be any antiderivative of <math style="vertical-align: -5px">f.</math>
 
|-
 
|
 
:&nbsp;&nbsp; Then, <math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a).</math>
 
 
|-
 
|-
|&nbsp;&nbsp; <math>F'(x)=\frac{\sin(x)}{1+\cos^{10}x}</math>
+
|&nbsp;&nbsp; &nbsp; &nbsp; <math>F'(x)=\frac{\sin(x)}{1+\cos^{10}x}</math>
 
|}
 
|}
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Revision as of 11:19, 9 April 2017

State the fundamental theorem of calculus, and use this theorem to find the derivative of


Foundations:  
What does Part 1 of the Fundamental Theorem of Calculus
say is the derivative of  

     First, we need to switch the bounds of integration.

     So, we have  

     By Part 1 of the Fundamental Theorem of Calculus,  


Solution:

Step 1:  
The Fundamental Theorem of Calculus, Part 1

Let    be continuous on    and let  

Then,    is a differentiable function on    and  

The Fundamental Theorem of Calculus, Part 2

Let    be continuous on    and let    be any antiderivative of   Then,

       

Step 2:  
First,
       
Now, let    and  
Therefore,

       

Hence,
       
by the Chain Rule.
Step 3:  
Now,
       
By the Fundamental Theorem of Calculus,

       

Hence,

       


Final Answer:  
        See Step 1 above
      

Return to Sample Exam